Recados para um devir: regeneração biocultural feminina no Médio Jequitinhonha - Gabriela Moulin Mendonça (2023)
This research is based on meetings with women from the Middle Jequitinhonha region, in Minas Gerais, and on the learning of the messages that pass between them and between them and the plants. These messages are intrinsic to their words-voices-bodies and are understood here as messages for the world that urgently needs a more just, affective, and sustainable present-future. The hypothesis is that these messages show us ways out for the reinvention of life, by way of the biocultural feminine restoration. The text intends to develop three analytical axes: the first concerns the telluric dimension, the experience of the land and territoriality, bringing discretionary and historical elements to the understanding of ambience and landscape; the second is the dimension of affection and joy, posing us challenges to talk about the loving ethics as a driver of change and well-living; and finally, the third, the ground of practices, which concerns the trajectory of some women of the quilombola community of Curtume, in Jenipapo de Minas (MG), and our translational practice of exchanging messages.